2006
DOI: 10.1889/1.2433403
|View full text |Cite
|
Sign up to set email alerts
|

63.3: Active-Matrix Cathodes with Tapered Macro-Gate for High-Performance Field Emission Display

Abstract: A color field emission display was developed with active-matrix cathodes and tapered macro-gate (TMG). The cascade-connected a-Si TFTs exhibited well controlled field emissions from carbon nanotube (CNT) emitters. The TMG protected the CNT emitters from the anode field perfectly, enabling us to apply a high anode voltage over 10 kV. IntroductionSince the first application of carbon nanotube (CNT) as an electron source, there were many attempts to make CNT-field emission display (FED) [1][2][3][4]. To construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Superaligned carbon nanotube (CNT) yarn and film have supplied the possibility for the fabrication of CNT devices at large area scale with high uniformity. For the advantages such as fast response, monochromatic, high brightness, and low power consumption, field emission is a very hot topic for the application of nanomaterials, especially for one-dimensional materials due to their high aspect ratio. Field emission of CNT has been widely studied for their exceptional field emission properties, ,, and it has been reported that superaligned CNT yarn has shown excellent field emission properties. The application of superaligned CNT yarn in field emission is possible to facilitate the fabrication of large area field emission display (FED) with improved performance, which requires a low cost fabrication process for mass production. The CNT yarn is difficult to integrated into the conventional vertical FED structures, which is adopted by the CNT paste and Spindt tip. ,, Itoh and et al have fabricated a planar type field emission structure in ref .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Superaligned carbon nanotube (CNT) yarn and film have supplied the possibility for the fabrication of CNT devices at large area scale with high uniformity. For the advantages such as fast response, monochromatic, high brightness, and low power consumption, field emission is a very hot topic for the application of nanomaterials, especially for one-dimensional materials due to their high aspect ratio. Field emission of CNT has been widely studied for their exceptional field emission properties, ,, and it has been reported that superaligned CNT yarn has shown excellent field emission properties. The application of superaligned CNT yarn in field emission is possible to facilitate the fabrication of large area field emission display (FED) with improved performance, which requires a low cost fabrication process for mass production. The CNT yarn is difficult to integrated into the conventional vertical FED structures, which is adopted by the CNT paste and Spindt tip. ,, Itoh and et al have fabricated a planar type field emission structure in ref .…”
mentioning
confidence: 99%
“…Field emission of CNT has been widely studied for their exceptional field emission properties, ,, and it has been reported that superaligned CNT yarn has shown excellent field emission properties. The application of superaligned CNT yarn in field emission is possible to facilitate the fabrication of large area field emission display (FED) with improved performance, which requires a low cost fabrication process for mass production. The CNT yarn is difficult to integrated into the conventional vertical FED structures, which is adopted by the CNT paste and Spindt tip. ,, Itoh and et al have fabricated a planar type field emission structure in ref . Canon and Toshiba have fabricated surface-conduction electron-emission display (SED), , which is also a planar type structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] The intrinsic FE of singlewalled CNTs was found to follow the Fowler-Nordheim ͑FN͒ theory, although adsorption effects induced nonlinearity in the FN ͑ln I / V 2 -1 / V͒ curves and produced current saturation phenomena. 9,12 Although the FE of multiwalled CNTs ͑MWCNTs͒ has been studied thoroughly, [5][6][7][8][13][14][15][16] the explanation of the deviation of their FE from FN theory is still controversial. [17][18][19] The details of the deviation of real FN curves from FN theory need to be properly explained for both practical and theoretical reasons.…”
Section: Introductionmentioning
confidence: 99%